SAT0455 Prevalence of behçet's disease in south-west germany among the adult turkish and german population. (23rd January 2014) - Riewerts, F.; Henes, J.C.; Deuter, C.; Lorenz, H.-M.; Mackensen, F.; Döhner, H.; Peter, H.H.; Kötter, I.
Abstract : Objectives: To estimate the prevalence of Behçet's disease (BD) among the adult Turkish and German population in Southern Wuerttemberg and Baden-Wuerttemberg. Methods: The study was conducted using two sources: A questionnaire was sent to 8000 general practitioners, rheumatologists, internal specialists, orthopaedic specialists, dermatologists, ENT-specialists and ophthalmologists in Southern Wuerttemberg. In addition, a random sample of 96 physicians of the same specialities was taken. Furthermore, all university hospitals, hospitals of maximum medical care and rheumatologists in Baden-Wuerttemberg were contacted. Then the results were correlated to the population of Southern Wuerttemberg and Baden-Wuerttemberg, based on data of the State Statistics Office. The prevalences were calculated per 100.000 inhabitants with indication of the 95%>confidence interval (CI, exact Poisson CI). Results: 31 patients were reported in Southern Wuerttemberg and 200 patients in Baden-Wuerttemberg. The prevalence among the Turkish population is 34, 44/100.000 in Southern Wuerttemberg and27, 71/100.000 in Baden-Wuerttemberg, considering the migration background. The prevalence among the German population does not differ between the two regions and amounts to 0, 82/100.000 inhabitants. When correlated to inhabitants without migration background, the prevalence is much higher (1, 05/100.000). Conclusions: The prevalence of BD among the Turkish population in Germany is much lower than in Turkey, where it is in the range between 80-420/100.000. This supports other studies which proposed strong environmental influences on the expression of BD. Furthermore a south-north-disparity becomes apparent. Similar results have also been described for Japan. The prevalence in the German population is comparable to the prevalence in other north-western European populations. The difference to the prevalence in Berlin, the highest nationwide with 1, 47/100.000 inhabitants, is probably caused by the multi-ethnic character of the urban Berlin population or immigrants from high-prevalence countries, as only patients with German nationality (not subtracting people with migration background) probably have been counted in Berlin. However, our results for people with German nationality (passport) are even lower with 0.82/100.000. Hence, another probable reason for this difference is a difference in methodology of the Berlin and the present study, which cannot be commented on, as no data on the methodology of the Berlin study are available. The present study is the first one to study the prevalence of BD in a defined region in Germany with a prospective approach (not registry-based) and considering the migration background. Disclosure of Interest: None Declared